Investigating the Reliability and Validity of the Persian Version of the Fullerton Advanced Balance Scale in Children with Higher Gross Motor Function Cerebral Palsy - Maryam Torabian (Iranian Rehabilitation Journal)
Background and Objectives: This study investigates the reliability and validity of the Iranian version of the Fullerton advanced balance scale in children with higher gross motor function cerebral palsy. Methods: A total of 56 children with cerebral palsy (6.59 ± 1.84 years) were diagnosed with level I or II adhering to the gross motor function classification system and 56 healthy children who matched them with age and gender contributed to this cross-sectional study. The Iranian version of the Fullerton advanced balance scale and The Persian version of the pediatric Berg balance scale were completed. The internal consistency, test-retest reliability, content, discrimination, and concurrent validity of the Iranian version of the Fullerton advanced balance scale were examined in children with higher gross motor function cerebral palsy. Results: Good test-retest reliability (intraclass correlation coefficient = 0.99), excellent internal consistency (Cronbach α coefficient = 0.98), standard error of the mean = 0.22, minimal detectable change = 1.83 and statistical disclosure control = 0.61 were found for the Iranian version of Fullerton advanced balance scale. All items had good content validity. The Spearman rank correlation coefficients between the Iranian version of the Fullerton advanced balance scale and the pediatric Berg balance scale indicated good concurrent validity (r = 0.91, P < 0.001). The area under the curve of 0.96 (95% confidence interval: 0.93 - 0.99) and a cut-off value of 31.5 (sensitivity: 0.89, and specificity: 0.11) of the Iranian version of the Fullerton advanced balance scale were detected. Conclusion: The Iranian version of the Fullerton advanced balance scale could be useful as a valid and reliable tool for assessing balance function in children with cerebral palsy; however, it is more concise and requires less time to execute.